Gaze Coordination of Groups in Dynamic Events – A Tool to Facilitate Analyses of Simultaneous Gazes Within a Team - Fasold, Frowin; Nicklas, André; Seifriz, Florian; Schul, Karsten; Noël, Benjamin; Aschendorf, Paula; Klatt, Stefanie (Frontiers in Psychology, 2021)
The performance and the success of a group working as a team on a common goal depends on the individuals’ skills and the collective coordination of their abilities. On a perceptual level, individual gaze behavior is reasonably well investigated. However, the coordination of visual skills in a team has been investigated only in laboratory studies and the practical examination and knowledge transfer to field studies or the applicability in real-life situations have so far been neglected. This is mainly due to the fact that a methodological approach along with a suitable evaluation procedure to analyze the gaze coordination within a team in highly dynamic events outside the lab, is still missing. Thus, this study was conducted to develop a tool to investigate the coordinated gaze behavior within a team of three human beings acting with a common goal in a dynamic real-world scenario. This team was a (three-person) basketball referee team adjudicating a game. Using mobile eye-tracking devices and an indigenously designed software tool for the simultaneous analysis of the gaze data of three participants, allowed, for the first time, the simultaneous investigation of the coordinated gaze behavior of three people in a highly dynamic setting. Overall, the study provides a new and innovative method to investigate the coordinated gaze behavior of a three-person team in specific tasks. This method is also applicable to investigate research questions about teams in dynamic real-world scenarios and get a deeper look at interactions and behavior patterns of human beings in group settings (for example, in team sports).